Pengaruh Penggunaan Media Audio Visual Pada Pembelajaran Pendidikan Agama Kristen Terhadap Minat Belajar Siswa Kelas VIII SMP Negeri 1 Pakkat Tahun Pembelajaran 2023/2024 - Santri Tenjun Boa Siringoringo; Eben H Telaumbanua; Andrianus Nababan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The research aims to determine the positive and significant influence of the use of audio-visual media in Christian Religious Education learning on the learning interest of class VIII students at SMP Negeri 1 Pakkat for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the use of audio-visual media in Christian Religious Education learning on the learning interest of class VIII students at SMP Negeri 1 Pakkat for the 2023/2024 academic year. Descriptive and inferential quantitative research methods. The population of all class VIII students at SMP Negeri 1 Pakkat for the 2023/2024 academic year who are Protestant Christians is 152 people. Random sampling (random sampling) was 35% of the total population, namely 53 people. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value rcount=0.501>rtabel(n=53)=0.297 and tcount=4.134>ttable(n-2=51)=2.000 shows that there is a relationship between the use of audio-visual media in Christian Religious Education learning and interest studying class VIII students of SMP Negeri 1 Pakkat for the 2023/2024 academic year. b) Regression equation. c) The determination test shows that the magnitude of the effect is 25.10%. d) Hypothesis testing obtained Fcount=16.794>Ftable(n-2=51)=3.15 so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the use of audio-visual media in Christian Religious Education learning on the learning interest of class VIII students at SMP Negeri 1 Pakkat for the 2023/2024 academic year.